2001
DOI: 10.1093/protein/14.11.845
|View full text |Cite
|
Sign up to set email alerts
|

The (βα)8 glycosidases: sequence and structure analyses suggest distant evolutionary relationships

Abstract: There are currently at least nine distinct glycosidase sequence families which are all known to adopt a TIM barrel fold [Henrissat,B. and Davies,G. (1997) CURR: Opin. Struct. Biol., 7, 637-644]. To explore the relationships between these enzymes and their evolution, comprehensive sequence and structure comparisons were performed, generating four distinct clusters. The first cluster, S1, comprises the alpha-amylase related enzymes, all with the retention mechanism (axial-->axial). The second cluster, S2, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
2
47
0
1
Order By: Relevance
“…The relationship between protein fold and function is complex, 35 thus proteins with the same fold can perform many diverse biological functions [77][78][79][80] and conversely, the same function can be carried out by more than one protein fold. 16 These two claims are demonstrated by the diversity of functions of enzymes that fold as TIM barrels 81,82 (TIM barrel folds are associated Figure 6. Identification of active sites, which are formed by more than one chain, although the catalytic residues are located on a single chain.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between protein fold and function is complex, 35 thus proteins with the same fold can perform many diverse biological functions [77][78][79][80] and conversely, the same function can be carried out by more than one protein fold. 16 These two claims are demonstrated by the diversity of functions of enzymes that fold as TIM barrels 81,82 (TIM barrel folds are associated Figure 6. Identification of active sites, which are formed by more than one chain, although the catalytic residues are located on a single chain.…”
Section: Discussionmentioning
confidence: 99%
“…More characteristic of family 1 ␤-glycosidases (53,56), the I170T active site opening is considerably different from that of the wild type model in which aromatic residues, the sugar binding subsites (see above), protrude into the narrow cleft. At the bottom of both are the highly conserved glutamates, Glu-164 and Glu-349, the catalytic acid and nucleophile, respectively, of family 1 glycosyl hydrolases (22,23,53,57). The threonine for isoleucine substitution at residue 170, replacing a hydrophobic residue with a noncharged polar side chain, also changes the geometry of its immediate vicinity, presumably making new hydrogen bonds and "tightening" the turns of the short coil structure of which it is a part.…”
Section: Figmentioning
confidence: 99%
“…In the absence of a published crystal structure for WT GghA, a three-dimensional molecular model, based on sequence homology to Paenibacillus polymyxa (21), was derived for both wild type (WT) and mutant GghA proteins. Our analysis of the parent and mutant apoenzymes was facilitated by the breadth of structural data available for family 1 glycosyl hydrolases (22): the conservation of the eightstranded TIM barrel-fold (23); the known residues involved in positioning and substrate recognition (24 -26); the mechanism of hydrolysis by general acid catalysis and the condition of specific residues in the active site microenvironment (27,28). Comparing the enhanced GghA apoenzyme to known family 1 structures enabled us to suggest how its single amino acid substitution produces the observed functional improvement.…”
mentioning
confidence: 99%
“…In fact, TIM domain in a form of eight b/a chains folded into barrel structure (Fig. 3) is a largely abundant structural component found in varying enzymes [23][24][25][26], and it is currently assigned to more than half of glycosyl hydrolases as a structural component. In addition, several studies of glycosyl hydrolases showed that the TIM barrel domain is responsible for the actual catalytic activity.…”
Section: Resultsmentioning
confidence: 99%